Diterpenoids and Triterpenoids From Frankincense Are Excellent Anti-psoriatic Agents: An in silico Approach - Halim, Sobia Ahsan; Khan, Ajmal; Csuk, Rene; Al-Rawahi, Ahmed; Al-Harrasi, Ahmed (Frontiers in Chemistry, 2020)
Psoriasis is a chronic autoimmune disease that affects 2–3% of the global population and requires an effective treatment. Frankincense has been long known for its potent anti-inflammatory activities. In this study, a structural bioinformatics approach was used to evaluate the efficacy of individual active components of frankincense, macrocyclic diterpenoid derivatives (1-27), and boswellic acids (28-46) in the treatment of psoriasis. Initially, major druggable targets of psoriasis were identified. Subsequently, structure-based screening was employed by using three different docking algorithms and scoring functions (MOE, AutoDock Vina, and MVD) for the target fishing of compounds against 18 possible targets of psoriasis. Janus Kinase 1, 2, 3 (JAK 1/2/3), eNOS, iNOS, interleukin-17 (IL-17), and Tumor necrosis factor-α (TNF-α) were identified as the preferred molecular targets for these compounds. This computational analysis reflects that frankincense diterpenoids and triterpenoids can serve as excellent anti-psoriatic agents by targeting major cytokines (TNF-α, IL-17, IL-13, IL-23, and IL-36γ,) exacerbated in psoriasis, and inflammatory pathways particularly JAK1/2/3, eNOS, iNOS, MAPK2, and IFNγ. The results were compared with the reported experimental findings which correlates well with our in-silico verdicts.